QGIS-Landsat Indices plugin (Q-LIP): Tool for environmental indices computing using Landsat data. (March 2021) - Sebbah, Boutaina; Yazidi Alaoui, Otmane; Wahbi, Miriam; Maâtouk, Mustapha; Ben Achhab, Nizar
Abstract: Environmental monitoring has become of paramount importance for researchers and decision makers in order to better protect the environment and achieve sustainable development goals, especially with continuous population growth and rapid urbanization and industrialization processes that alter natural components of the environment and degrade the ecosystems. Hence, the use of Landsat data is of great significance, particularly in environmental monitoring and land management, due to their high spatial resolution and their free of cost availability since 1972. However, calculation of remotely sensed indices for environmental purpose occurs in several steps and requires minimum knowledge in imagery processing. This paper describes the development and design of Q-LIP "QGIS-Landsat Indices plugin"- a simple and easy-to-use tool to download, process and automatically calculate environmental indices from Landsat imagery. Q-LIP has been built under Python and designed as a QGIS software plugin; it is available to download from QGIS Plugin Repository. Highlights: Q-LIP is an easy-to-use tool for computing environmental indices from Landsat data. Q-LIP is created as QGIS plugin that allows downloading, preprocessing and computing environmental indices. It is designed to reduce processing time and serve users with poor knowledge in image processing. Outputs of plugin are of great interest for researchers and decision makers in environmental monitoring and land management.